Maximizing Flow and Ensuring Leak Tightness Through Design and Development of a Unidirectional Check Valve - Sachin S.; P.V. Srihari (International Journal of Industrial and Product Design Engineering, 2024)
The check valve market, valued at USD 6.5 billion in 2024, is expected to grow at a 4.1% CAGR. Challenges in valve seat materials, particularly SS304 and PTFE (Teflon), contribute to a 0.5% leak rate, which leads to helium gas loss, reduced efficiency, and higher operational costs. While various sealing techniques, including hard-on-soft methods, have been explored, few have been applied to poppet check valves. This study focuses on improving sealing capacity with a hard-on-soft seat design to create a unidirectional valve capable of supporting a 5 g/s flow rate at 7 bar, with a leak tightness below 1x10-4 scc/s. The valve was designed in Fusion 360, utilizing SS304 and Teflon for key components like the seat and poppet. Leak testing, conducted at 5 g/s and 7 bar, used a Helium Leak Detector (HLD 550 Pfeiffer) and confirmed a minimal leak rate of 1.1 × 10⁻⁴ scc/s. CFD simulations in ANSYS 2024 R1 were performed to analyze fluid flow, pressure distribution, and valve efficiency, achieving 90% accuracy with stable residuals. Both experimental testing and CFD analysis supported the valve’s enhanced sealing and reverse flow prevention. Future work may involve advanced wear-resistant coatings, alternative spring designs, and automated leak detection systems to improve durability, responsiveness, and production efficiency
Keywords: CFD simulation; PTFE; SS304; Unidirectional check valve; flow optimization; leak tightness